Upaya Perbaikan Downtime pada Mesin Dryer Menggunakan Metode Overall Equipment Effectiveness di PT. ABC - Riyana, Iis; Hamidah, Nur; Sulistyowati, Enik; Diana, Alfi Nur (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
High downtime in production machines is one of the main obstacles that hinder the achievement of production targets in the manufacturing industry. PT Syngenta Seed Indonesia, particularly in the plant dryer section, experiences significant downtime issues on the dryer machine, which impacts the failure to meet the corn seed yield targets. This study aims to measure the effectiveness of the dryer machine and identify the root causes of downtime in order to propose appropriate corrective actions. The method used is Overall Equipment Effectiveness (OEE) measurement, which consists of three main components: availability, performance, and quality. The results of the study show that the average OEE value is 48%, far below the world-class standard of 85%. The average values for availability, performance, and quality are 66%, 75%, and 97%, respectively. The main causes of the low OEE value are high downtime due to material waiting times, machine overheating, and operator handling errors. Based on these findings, proposed improvements include operator training, rescheduling preventive maintenance, temperature sensor repairs, and adjustments to the drying process information system.